Normal Numbers of Stem Cell Memory T Cells Despite Strongly Reduced Naive T Cells Support Intact Memory T Cell Compartment in Ataxia Telangiectasia - Weitering, Thomas J.; Melsen, Janine E.; van Ostaijen-ten Dam, Monique M.; Weemaes, Corry M. R.; Schilham, Marco W.; van der Burg, Mirjam (Frontiers in Immunology, 2021)
Ataxia Telangiectasia (AT) is a rare inherited disorder characterized by progressive cerebellar ataxia, chromosomal instability, cancer susceptibility and immunodeficiency. AT is caused by mutations in the ATM gene, which is involved in multiple processes linked to DNA double strand break repair. Immunologically, ATM mutations lead to hampered V(D)J recombination and consequently reduced numbers of naive B- and T-cells. In addition, class switch recombination is disturbed resulting in antibody deficiency causing common, mostly sinopulmonary, bacterial infections. Yet, AT patients in general have no clinical T-cell associated infections and numbers of memory T cells are usually normal. In this study we investigated the naive and memory T-cell compartment in five patients with classical AT and compared them with five healthy controls using a 24-color antibody panel and spectral flow cytometry. Multidimensional analysis of CD4 and CD8 TCRαβ+ cells revealed that early naive T cell populations, i.e. CD4+CD31+ recent thymic emigrants and CD8+CCR7++CD45RA++ T cells, were strongly reduced in AT patients. However, we identified normal numbers of stem cell memory T cells expressing CD95, which are antigen-experienced T cells that can persist for decades because of their self-renewal capacity. We hypothesize that the presence of stem cell memory T cells explains why AT patients have an intact memory T cell compartment. In line with this novel finding, memory T cells of AT patients were normal in number and expressed chemokine receptors, activating and inhibitory receptors in comparable percentages as controls. Comparing memory T cell phenotypes by Boolean gating revealed similar diversity indices in AT compared to controls. We conclude that AT patients have a fully developed memory T cell compartment despite strongly reduced naive T cells. This could be explained by the presence of normal numbers of stem cell memory T cells in the naive T cell compartment, which support the maintenance of the memory T cells. The identification of stem cell memory T cells via our spectral flow cytometric approach is highly relevant for better understanding of T cell immunity in AT. Moreover, it provides possibilities for further research on this recently identified T cell population in other inborn errors of immunity.